2017
DOI: 10.1007/s00330-017-4991-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the stand-alone synthetic image in digital breast tomosynthesis examinations

Abstract: • Stand-alone SI demonstrated performance not inferior for lesion visibility as compared to FFDM. • Stand-alone SI demonstrated performance not inferior for lesion BIRADS categorisation as compared to FFDM. • Synthetic images provide important dose savings in breast tomosynthesis examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Specificity was shown to be lower for microcalcifications and higher for distortions 45. In more recent studies, a similar specificity between SM and DM, with or without DBT, was found 44,97,98. In conclusion, specificity was shown to be at least equivalent for Hologic DM and SM, and higher for DBT&SM when compared to DM alone.…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosysupporting
confidence: 55%
See 2 more Smart Citations
“…Specificity was shown to be lower for microcalcifications and higher for distortions 45. In more recent studies, a similar specificity between SM and DM, with or without DBT, was found 44,97,98. In conclusion, specificity was shown to be at least equivalent for Hologic DM and SM, and higher for DBT&SM when compared to DM alone.…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosysupporting
confidence: 55%
“…The TOMMY trial, with 7060 participants, has shown an overall sensitivity of 87% for DM alone, and 88% for DBT&SM, ie not a significant difference between the two 45,51. Similar results were found specifically for microcalcifications 97,98. In two other studies a different there was an increased sensitivity by SM and DBT&SM compared to DM alone 43,44…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 59%
See 1 more Smart Citation
“…We collected sets of DM examinations that were read by multiple radiologists during other unrelated, and previously completed, retrospective multi-reader multi-case (MRMC) observer studies (25)(26)(27)(28)(29)(30)(31)(32). In those studies, DM was compared to another modality (eg, digital breast tomosynthesis) for breast cancer detection in cancer-enriched datasets.…”
Section: Digital Mammogramsmentioning
confidence: 99%
“…According to a recent Spanish observational, retrospective, single-centre, multireader blinded study, the performance of stand-alone synthetic image mammography was not inferior for lesion visibility and for lesion BIRADS categorisation as compared with full-field DM. 18 …”
Section: Introductionmentioning
confidence: 99%